ANALISIS JARINGAN KOMUNIKASI RISIKO PETANI BAWANG MERAH: STUDI KASUS KELOMPOK TANI RINDU ALAM DESA CIKAWAO, PROVINSI JAWA BARAT - Harlina, Raesa; Fatimah, Sri; Setiawan, Iwan (Jurnal AGRISEP, 2018)
Risk perceptions needs to be developed through risk communication. Without it, farmers' awareness risks is low. The paper is aimed to explain risk communication in Rindu Alam Farmer Group using Social Network Analysis (SNA) Method.  Cultivating vegetables on high land may cause landslide. The result is Risk communication is mostly done directly. The type of social network in this group is the whole network. The density of network is 0.369 with medium strength, number of bonds are 114. Actors who have the highest degree of closeness, betweenness and centrality are the organizer of the group. The most frequently communicated risk factors are production, price, and market.